BMP-6 over-expression in prostate cancer is associated with increased Id-1 protein and a more invasive phenotype. - Darby, S; Cross, S; Brown, N; Hamdy, F; Robson, C (2008)
Bone morphogenetic protein-6 (BMP-6) has been strongly implicated in prostate cancer development and bone metastasis. Our previous data showed that BMP-6 mRNA was absent in patients with benign prostatic hyperplasia, but evident in primary tumours with established secondary skeletal metastases. To examine the role of BMP-6 in prostate cancer progression, we have developed a BMP-6-regulatable, doxycycline-inducible gene expression system. BMP-6 induction by doxycycline addition led to increased levels of BMP-6 RNA and protein, associated with nuclear translocation of SMADs and activation of the downstream target gene Id-1. BMP-6 protein did not enhance the proliferation rate of PC3M cells but did significantly increase the rate of migration and invasion in both PC3M and DU145 cells. Increased metalloproteinase (MMP-1 and MMP-9) mRNA levels were also observed following BMP-6 induction. Luciferase reporter assays confirmed BMP-6-mediated activation of MMP-1 and MMP-9 promoters, indicating direct transcriptional activation of MMPs by BMP-6. BMP-6 stimulation also led to an increase in phosphorylation levels of MAPK proteins. We next examined the effects of BMP-6 on the downstream gene Id-1 in a cohort of prostate cancer patients. A tissue microarray (TMA) was constructed and samples stained for BMP-6 and Id-1 expression. We observed a significant increase in the intensity of staining of epithelial BMP-6 in the cancer cases compared to the benign cases (Mann-Whitney U test, p < 0.0005) and in the intensity of staining of epithelial Id-1 in the cancer cases compared to the benign cases (Mann-Whitney U test, p = 0.015). We further observed a significant positive correlation between epithelial staining for Id-1 and BMP-6 (p = 0.001) across all samples for both benign and cancer cases. These data demonstrate that BMP-6 promotes migration and invasion of prostate cancer cells, potentially through activation of Id-1 and MMP activation.